Development of Protective Inflammation and Cell-Mediated Immunity against Cryptococcus neoformans after Exposure to Hyphal Mutants - Bing Zhai (American Society for Microbiology, 2015)
ABSTRACT Morphological switch is tightly coupled with the pathogenesis of many dimorphic fungal pathogens. Cryptococcus neoformans, the major causative agent of cryptococcal meningitis, mostly presents as the yeast form but is capable of switching to the hyphal form. The filamentous form has long been associated with attenuated virulence, yet the underlying mechanism remains elusive. We previously identified the master regulator Znf2 that controls the yeast-to-hypha transition in Cryptococcus. Activation of Znf2 promotes hyphal formation and abolishes fungal virulence in vivo. Here we demonstrated that the cryptococcal strain overexpressing ZNF2 elicited strong and yet temporally confined proinflammatory responses in the early stage of infection. In contrast, exacerbated inflammation in mice infected with the wild-type (WT) strain showed that they were unable to control the infection. Animals inoculated with this filamentous Cryptococcus strain had fewer pulmonary eosinophils and CD11c+ CD11b+ cells than animals inoculated with WT yeast. Moreover, mice infected with this strain developed protective Th1- or Th17-type T cell responses. These findings suggest that the virulence attenuation of the filamentous form is likely due to its elicitation of protective host responses. The antivirulence effect of Znf2 was independent of two previously identified factors downstream of Znf2. Interestingly, mucosal immunizations with high doses of ZNF2-overexpressing cells, either in the live or heat-killed form, offered 100% protection to the host from a subsequent challenge with the otherwise lethal clinical strain H99. Our results demonstrate that heat-resistant cellular components presented in cryptococcal cells with activated ZNF2 elicit protective host immune responses. These findings could facilitate future research on novel immunological therapies. IMPORTANCE Cryptococcal meningitis is one of the leading causes of death among AIDS patients. This disease presents a severe threat to public health. The current antifungal regimens are unsatisfactory in controlling or clearing the pathogen Cryptococcus neoformans. Immunotherapies and/or vaccines could be a promising approach to prevent or manage this deadly disease. However, the lack of understanding of host-pathogen interactions during cryptococcal infection greatly hampers the development of effective immunotherapies. In this study, we discovered that inoculation of cryptococcal cells with activated Znf2, a morphogenesis regulator and an antivirulence factor, could shift the host pathological Th2 responses to the protective Th1 or Th17 responses. Importantly, we discovered that vaccination with either the viable or heat-killed form of ZNF2-overexpressing cells protected animals from the otherwise lethal infection by the highly virulent clinical strain. Our study suggests that the fungal cellular component(s) of the ZNF2-overexpressing strain may provide potential vaccine candidate(s) for controlling the fatal disease.